On Ethnographic Genre and the Experience of Communal Work with the Hutterian People - Stephenson, Peter H. (Culture, 1986)
This paper takes the problem of describing Hutterite work as a point of departure to discuss several problematic aspects of ethnographic genre and writing. The analytic mode of ethnography when applied to Hutterians compounds the stereotype of a dour people so the author utilizes humour and pathos to describe Hutterites at work and moves throughout from description and dialogue to interpretation instead of from generalization to illustration as is more conventional in the format of ethnographic writing. The authoritative voice of the narrator eventually yields to the description of an experience where neither the ethnographer nor his subjects were in control of events. This final scene serves as a metaphor for fieldwork and suggests that many of the problems associated with writing as an inherently destructive analytical mode can be transcended. The nature of this transcendence is suggested by the writer who shapes a story and completed by the reader who hears what is said — if only in the mind’s eye — through a suspension of disbelief.